Correlation of Non-Financial Compensation and Work Loyalty of Administrative Employees at Madrasah Aliyah Negeri in Bandung - Sulhan, Moh.; Gustini, Neng; Sambella, Mutiara; Hali, Ali Usman (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2024)
This study aimed to 1) identify the description of non-financial compensation at the State Aliyah Madrasah in Bandung, 2) describe administrative work loyalty at the State Aliyah Madrasah in Bandung, and 3) analyze the relationship between non-financial compensation and the work loyalty of administrative employees at the State Aliyah Madrasah in Bandung. This study employs a quantitative approach with ex post facto methods. The sample consists of 39 administrative employees selected using a non-probability sampling method with a purposive sampling technique. Data collection was conducted through questionnaires, and the data analysis technique utilized the SPSS 26 program. The results indicate that the non-financial compensation variable received an outstanding respondent's response of 88.17%, with the Reality (X) Non-financial compensation variable falling into the "Very High" category due to its interval range of 4.20-5.00 and obtaining a value of 4.40. The Reality variable (Y), Job Loyalty, also falls into the "Very High" category, with an interval range of 4.20-5.00 and a value of 4.33. The correlation coefficient value is 0.612, indicating a strong positive relationship as it falls within the range of 0.61 – 0.80.